Analisis Efektivitas Investasi Perusahaan Daerah Pasar Resik Kota Tasikmalaya - Rustandi, Andi (WELFARE Jurnal Ilmu Ekonomi, 2020)
PD Pasar Resik can ideally make a major contribution to the regional revenue source of the City of Tasikmalaya. Investment Tasikmalaya City Government established and included capital for PD Pasar Resik initially to be able to manage traditional markets in a professional manner, but in its development even faced many problems for regional finance. Not only does it fail to be a source of revenue, it even burdens regional finances. The purpose of the study evaluates the effectiveness of government investment as well as the operational feasibility of PD Pasar Resik in Tasikmalaya City. Using descriptive methods based on collecting time series data through surveys, documentation and literature studies. Investment analysis is conducted using measurements of Earning Power of Total Investment (EpoTI), Rate of Return Investment (ROI), and Rate of Return on Net Worth (RoRoNW) or Rate of Return for the Owners. As a result, investments cannot be effectively managed due to complex problems, and PD Pasar Resik's operations are no longer effective or feasible.Pasar Resik idealnya dapat memberikan kontribusi besar bagi sumber penerimaan daerah Kota Tasikmalaya. Investasi Pemerintah Kota Tasikmalaya mendirikan dan menyertakan modal bagi Perusahaan Daerah (PD) Pasar Resik awalnya agar dapat mengelola pasar-pasar tradisional secara profesional, namun dalam perkembangannya malah menghadapi banyak masalah bagi keuangan daerah. Tidak hanya gagal menjadi sumber penerimaan, bahkan membebani keuangan daerah. Tujuan penelitian mengevaluasi efektivitas investasi pemerintah serta kelayakan operasional PD. Pasar Resik di Kota Tasikmalaya. Menggunakan metode deskriptif berdasarkan pengumpulan data runtun waktu melalui survei, studi dokumentasi dan literatur. Analisis investasi dilakukan mempergunakan pengukuran Earning Power of Total Investment (EpoTI), Rate of Return on Investment (ROI), dan Rate of Return on Net Worth (RoRoNW) atau Rate of Return for the Owners. Hasilnya, investasi tidak dapat dikelola efektif dikarenakan adanya masalah kompleks, serta operasional PD. Pasar Resik sudah tidak efektif dan tidak layak lagi.